The global model of constitutional rights - d (Oxford : Oxford University Press, 2012)
The rapid spread of judicially-enforced constitutional rights has been one of the most dramatic developments in modern law. This book argues that there is now a global model for how such rights should function, and develops an original philosophically grounded, account of their nature and scope.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Civil rights -- Philosophy; Constitutional law -- Philosophy